Revolutionary constitutionalism : law, legitimacy, power - Revolutionary Constitutionalism Conference (2018 : Yale Law School); Albert, Richard (Law professor) (Oxford ; Hart, 2020)
"Bruce Ackerman's path-breaking book on Revolutionary Constitutions: Charismatic Leadership and the Rule of Law puts him at the centre of the major subjects in public law today. From the promise and perils of populism to the causes and consequences of democratic backsliding, from the optimal models of constitutional design to the forms and limits of constitutional amendment, and from the role of courts in constitutional democracy to how we identify when the mythical "people" have spoken. Ackerman's pioneering book was the focus of a major international conference held at the Yale Law School. The conference convened leading scholars in public law to engage critically with Ackerman's thesis. Some advanced it, others attacked it, and still others refined it-but all agreed that the ideas in the book reset the terms of debate on the most important questions in constitutionalism today. This collection, edited by Richard Albert, emerges from the lively conference, and features a rebuttal chapter by Ackerman in which he responds directly to review essays by authors"--
Introduction : A Global Tour of Constitutionalism / Richard Albert -- A Political, not a Legal History of the Rise of Worldwide Constitutionalism / Dieter Grimm -- A Defence of Non-representational Constitutionalism : Why Constitutions Need not be Representational / Alon Harel -- Constitutionalism and Society : Ackerman on Worldwide Constitution-Making and the Role of Social Forces / Denis Baranger -- Bruce Ackerman's Theory of History / Roberto Gargarella -- Constitutionalism and the Predicament of Postcolonial Independence / Aziz Rana -- Revolution on a Human Scale : Liberal Values, Populist Theory? / Andrew Arato -- Charismatic Fictions and Constitutional Politics / Tom Ginsburg -- Uncharismatic Revolutionary Constitutionalism / Stephen Gardbaum -- Unconventional Adaptation and the Authenticity of the Constitution / Alessandro Ferrara -- Constitutional Revolution, Legal Positivism and Constituent Power / Yasuo Hasebe -- The Traditions of Constitutional Change / Richard Albert -- Constitutional Crossroads : A View from Europe / Neil Walker -- How Europe Brought Judicial Review to France : A Response to Bruce Ackerman / Daniel Halberstam -- Constituting the Judiciary, Constituting Europe / Mitchel Lasser -- Sustaining Revolutionary Constitutions : From Movement Party to Movement Court / Menaka Guruswamy -- The Italian Constitution as a Revolutionary Agreement / Marta Cartabia -- Constitutional Strategy for a Polarised Society : Learning from Poland's Post-revolutionary Misfortunes / Maciej Kisilowski -- Revolution as a Human Tale : Lessons from South Africa's Undecided Constitutionalism / James Fowkes -- The Race against Time / Bruce Ackerman.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Ackerman, Bruce A. -- Congresses; Constitutional law -- Congresses; Law; Electronic books